Exploring expert insights on early years risk and protective factors for long-term marital sustainability - Zafri, Aisya Vania; Juhari, Rumaya; Madon, Zainal; Arshat, Zarinah; Hasbullah, Muslihah (Human Resources Management Academic Research Society (HRMARS), 2024)
The first five years of marriage are a crucial period for sustaining relationships, especially in Malaysia, where a growing number of marriages end in divorce, with financial stress being a primary cause. This study explores marital sustainability through a qualitative approach, focusing on expert perspectives regarding the B40 group, Malaysia's lower-income households, during their critical first five years of marriage. The study utilizes a framework that incorporates both the risk and protective factors of marital sustainability, while also acknowledging the heightened vulnerability of marriages during the early years and shedding light on strategies for nurturing and sustaining marital bonds. In-depth interviews were conducted with experts (N=5) in the field of family studies. Using thematic analysis, the researchers identified key risk and protective factors influencing marital sustainability. Among the protective factors for marital sustainability are adaptability and willingness to change, effective communication, emotional and physical intimacy, mutual support and shared responsibilities, quality time together, spirituality, and emotional and instrumental support. However, the risk factors include lack of understanding, family interference, and financial stress. Interestingly, these factors do not differ from factors that would imply marital satisfaction or marital happiness. Implications and suggestions for future research were discussed further within the study.